Current molecular profile of juvenile nasopharyngeal angiofibroma: First comprehensive study from India. (31st August 2016) - Pandey, Praveen; Mishra, Anupam; Tripathi, Ashoak Mani; Verma, Veerendra; Trivedi, Ritu; Singh, Hitendra Prakash; Kumar, Sunil; Patel, Brijesh; Singh, Vinay; Pandey, Shivani; Pandey, Amita; Mishra, Subhash Chandra
Abstract : Objective: An attempt is made to analyze the molecular behavior of juvenile nasopharyngeal angiofibroma (JNA). Study Design: Case Series Methods: Quantification of mRNAs expression was undertaken through real‐time polymerase chain reaction in JNA (9–24) samples for VEGF‐A, basic fibroblast growth factor (b‐FGF), platelet‐derived growth factor PDGF‐A, KIT proto‐oncogene receptor tyrosine kinase (c‐Kit), Avian myelomatosis viral oncogene homolog (c‐Myc), Harvey rat sarcoma viral oncogene homolog (H‐Ras), tumor suppressor gene TP53, and androgen receptor and interleukin 6 (IL‐6). The β‐catenin expression was evaluated by western blot in 16 samples. Nasal polyp was taken as control. Results: A significantly increased ( P < 0.01) expression of c‐myc, VEGFA, bFGF, PDGFA, c‐kit, and TP53 was seen, along with enhanced expression of β‐catenin. A massive enhancement of H‐Ras expression was seen for the first time. Androgen receptor expression was no different, whereas IL‐6 despite showing upregulation trend was not significant. Conclusion: The enhanced expressions of various markers suggest their potential role in JNA. Although the biological significance of c‐kit, c‐myc, and one of the novel markers H‐Ras has yet to be defined, their significant expression may have a therapeutic importance. Level of Evidence: NA. Laryngoscope, 127:E100–E106, 2017